Pemegang Polis Asuransi Dan Kedudukan Hukumnya - Sunarmi ' (Jurnal Ilmu Hukum, 2012)
Insurance plays an important role, because in additionto providing protection against the possibilities oflosses that will happen, insurance gives a huge boostto the development of other economies. Unfortunatelyin practice guarantees legal protection of insurancepolicyholders are less protected. The problems ex-perienced by the policyholder is always the difficultyof obtaining payment of compensation when eve-nement happen. The reason why the policy is not paidby insurance companies is due to a lack of know-ledge of the community itself, but also because of theinsurance agent.